Malaria and its prevention: socio-acceptability in the application of insecticides-treated bed nets among household heads in the rural village community of Mazabuka, Zambia - Banda, Jane; Ithnin, Nur Raihana; Osman, Malina; Awang Hamat, Rukman (Universiti Putra Malaysia, 2023)
Introduction: Malaria poses immerse public health challenges in the world as it is still causing significant morbidity and mortality especially in endemic regions such as Zambia. One of the effective tools in preventing malaria is the application of insecticide-treated bed nets (ITNs). This study aims to explored the socio-acceptability of malaria and ITNs among rural village community of Mazabuka, Zambia. Methods: A semi-structured questionnaire was administered to 177 respondents via two different approached methods; focus group discussions and one-to-one interviews to assess the level of KAP of the respondents about malaria and ITNs. Results: Most of the respondents (98.7%) possessed ITNs that were provided free of charge by the Ministry of Health Zambia. Overall, the knowledge and attitude of respondents on malaria and ITNs were at moderate levels of 68.1% and 71.8%, respectively. In contrast, the level of practice was poor with only 36.2% of positive response. Although 92.1% of the respondents answered correctly on the association between malaria and mosquito bites, myths and misconceptions were still common as some of them still attributed malaria to drinking dirty waters (32.8%), bad weather (15.8%), witchcraft (3.4%), and bathing dirty water (19.8%). The practice was significantly associated with knowledge (p=0.003), but not attitude (p=0.230). Logistic regression analysis revealed that respondents with high knowledge level and tertiary education were more likely to use ITNs correctly (OR=2.957; OR=21.739, respectively). Conclusion: The present study showed that the knowledge gaps were remained among the villagers as misconceptions and their believe of myths were still exist.